2013
DOI: 10.1002/emmm.201201869
|View full text |Cite
|
Sign up to set email alerts
|

TSC22D4 is a molecular output of hepatic wasting metabolism

Abstract: In mammals, proper storage and distribution of lipids in and between tissues is essential for the maintenance of energy homeostasis. Here, we show that tumour growth triggers hepatic metabolic dysfunction as part of the cancer cachectic phenotype, particularly by reduced hepatic very-low-density-lipoprotein (VLDL) secretion and hypobetalipoproteinemia. As a molecular cachexia output pathway, hepatic levels of the transcription factor transforming growth factor beta 1-stimulated clone (TSC) 22 D4 were increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 46 publications
3
48
0
Order By: Relevance
“…In line with these fi ndings, the literature describes that liver-specifi c knockout of FASN does not rescue the animals from the development of a fatty liver ( 64 ) and Jones et al ( 65 ) recently reported the development of a steatosis in TSC22D4 overexpressing mice despite decreased FASN mRNA levels. Most interestingly, animals overexpressing ELOVL6 also show increased liver triglycerides and at the same time reduced FASN expression ( 20 ).…”
Section: Discussionmentioning
confidence: 66%
“…In line with these fi ndings, the literature describes that liver-specifi c knockout of FASN does not rescue the animals from the development of a fatty liver ( 64 ) and Jones et al ( 65 ) recently reported the development of a steatosis in TSC22D4 overexpressing mice despite decreased FASN mRNA levels. Most interestingly, animals overexpressing ELOVL6 also show increased liver triglycerides and at the same time reduced FASN expression ( 20 ).…”
Section: Discussionmentioning
confidence: 66%
“…Last, hepatic steatosis has been documented in CAC patients (Teli et al 1995). At the molecular level, hepatic gene expression of the transcription factor TGFβ1-stimulated clone 22 D4 (TSC22D4) is increased in experimental cachexia and correlates with the degree of systemic wasting (Jones et al 2013). Gene expression levels of the nuclear receptor cofactor receptor-interacting protein 140 (RIP140) are also increased in CAC and may contribute to liver steatosis by preventing the release of TG stores (Berriel Diaz et al 2008).…”
Section: The Role Of the Liver In Cancer Cachexiamentioning
confidence: 99%
“…Given the hypermetabolic and pro-inflammatory etiology of cachexia, disruption of liver functions could play a role in cachexia progression. Liver expression of TGFβ family transcription factor TSC22D4 correlates with body weight loss and VLDL hypo-secretion in the IL-6 dependent C26 cancer cachexia model [39]. Chronic IL-6 exposure during cachexia is also known to induce anemia and produce APPs, which provides further evidence of liver dysfunction [1, 28].…”
Section: The Liver As a Target Of Il-6mentioning
confidence: 99%